Novel environment-friendly catalyst system, preparation method and PBAT synthesis method

By using new catalyst systems with metal organic frame materials, organotin compounds and surfactants, the problem of traditional catalysts producing harmful by-products in PBAT synthesis is solved, and high-efficiency, low energy consumption and environmentally friendly PBAT synthesis is achieved, and the product is improved Performance and reduce environmental pollution risks.

CN119161568APending Publication Date: 2024-12-20BEIJING HUAFU ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411445606.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional catalysts produce harmful by-products during PBAT synthesis, resulting in an increase in environmental pollution risk and adversely affecting the performance of the final product.

Method used

A new environmentally friendly catalyst system consisting of metal organic frame materials, organotin compounds and surfactants is used to synthesize metal organic frame materials through hydrothermal method, and mix them with organotin compounds and surfactants in proportion, and use ultrasonic dispersion to form a stable Catalyst system for esterification and polycondensation of PBAT at lower temperatures.

Benefits of technology

It has achieved high catalytic efficiency, low energy consumption, and environmentally friendly PBAT synthesis. The product has excellent mechanical properties and high intrinsic viscosity, reducing environmental pollution, and the catalyst can be recycled and reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161568A_ABST
    Figure CN119161568A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of catalysts, and particularly relates to a novel environment-friendly catalyst system, a preparation method and a PBAT synthesis method, and the novel environment-friendly catalyst system for PBAT synthesis comprises a metal organic framework material, an organic tin compound and a surfactant. The method has high catalytic efficiency, the novel catalyst can realize efficient polymerization reaction at a low reaction temperature (160-180 DEG C), the molecular weight and yield of PBAT are significantly improved, the method is environmentally friendly, the used MOFs material and cocatalyst have low environmental influence, the catalyst can be recycled, environmental pollution in the production process is reduced, and the method is suitable for industrial production. Compared with a traditional catalyst, the novel catalyst can perform polymerization reaction at lower reaction temperature and pressure, the energy consumption is greatly reduced, and the PBAT synthesized by the method has excellent mechanical properties, higher intrinsic viscosity and better thermal stability, and is suitable for various application fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a novel environmentally friendly catalyst system, a preparation method and a PBAT synthesis method. Background Art

[0002] Polybutylene terephthalate-co-polybutylene adipate (PBAT) is an important biodegradable polymer material, which has attracted much attention due to its excellent mechanical properties, good biodegradability and wide application fields. PBAT is usually used in degradable plastic products, agricultural mulch films, packaging materials, etc. It has the potential to replace traditional plastics and meets the current needs of environmental protection and sustainable development.

[0003] At present, the industrial synthesis of PBAT is mainly carried out by direct esterification or transesterification, which usually rely on traditional catalyst systems such as tetrabutyl titanate, antimony compounds, etc. Although these catalysts can effectively catalyze the synthesis of PBAT, they have some obvious shortcomings. For example, catalysts such as tetrabutyl titanate are more active under high temperature conditions, but their catalytic activity is unstable, and higher temperatures and pressures are required during the reaction, resulting in high energy consumption. In addition, these traditional catalysts may produce harmful by-products during the reaction, increasing the risk of environmental pollution and may have an adverse effect on the performance of the final product. Summary of the invention

[0004] The purpose of the present invention is to provide a new environmentally friendly catalyst system to solve the problem that traditional catalysts may produce harmful by-products during the reaction process, increase the risk of environmental pollution, and may have an adverse effect on the performance of the final product.

[0005] The present invention is achieved by providing a new environmentally friendly catalyst system, wherein the new environmentally friendly catalyst system for synthesizing PBAT comprises: a metal organic framework material, an organic tin compound and a surfactant.

[0006] Preferably, the metal organic framework material is UiO-66, MIL-101 or ZIF-8, the organotin compound is dibutyltin oxide or dibutyltin dilaurate, and the surfactant is polyethylene glycol or sodium dodecyl sulfate.

[0007] Another object of the present invention is to provide a method for preparing the novel environmentally friendly catalyst system as described above, the method comprising:

[0008] To prepare the metal organic framework material, the metal salt and the organic ligand are mixed in a solvent to obtain a uniformly dispersed suspension;

[0009] Synthesizing a metal organic framework material by a hydrothermal method, obtaining a MOFs material precursor by cooling, filtering and washing a reaction product, and drying the product at 100° C. to 120° C. in a breaking gas atmosphere to obtain a metal organic framework material;

[0010] preparing a composite catalyst, mixing the prepared metal organic framework material with an organic tin compound and a surfactant in proportion;

[0011] Ultrasonic dispersion treatment or grinding treatment is used to ensure uniform mixing of the components to form a stable catalyst system, and the catalyst is dried at 50° C. to 70° C. to obtain a final catalyst product.

[0012] Preferably, in the step of adopting ultrasonic dispersion treatment, the frequency of ultrasonic dispersion treatment is 30 kHz and the time is 40 minutes.

[0013] Preferably, in the step of drying at 50°C to 70°C to obtain the final catalyst product, the drying condition is drying at 60°C for 12 hours.

[0014] Another object of the present invention is to provide a PBAT synthesis method based on the novel environmentally friendly catalyst system as described above, the method comprising preparing raw materials for PBAT synthesis, adding 1,4-butanediol, adipic acid and terephthalic acid into a reactor in a predetermined proportion, and adding an appropriate amount of the novel environmentally friendly catalyst system;

[0015] Esterification reaction: the esterification reaction is carried out at 160°C to 180°C to ensure that the esterification rate reaches 80% to 95%;

[0016] The polycondensation reaction is carried out by gradually raising the temperature to 200° C. to 230° C. under reduced pressure for 60 to 120 minutes to obtain a PBAT polymer.

[0017] Preferably, the polycondensation reaction time is 75 minutes and the esterification reaction temperature is 170°C.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) High catalytic efficiency. The new catalyst can achieve efficient polymerization reaction at a relatively low reaction temperature (160-180°C), significantly improving the molecular weight and yield of PBAT.

[0020] (2) Environmentally friendly: the MOFs materials and co-catalysts used have low environmental impact, and the catalysts can be recycled and reused, reducing environmental pollution during the production process.

[0021] (3) Low energy consumption. Compared with traditional catalysts, the new catalyst can carry out polymerization reactions at lower reaction temperatures and pressures, greatly reducing energy consumption.

[0022] (4) Excellent performance: the synthesized PBAT has excellent mechanical properties, high intrinsic viscosity and good thermal stability, and is suitable for a variety of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Fourier transform infrared spectra (FTIR) of different PBATs provided in embodiments of the present invention;

[0024] Figure 2a The embodiment of the present invention provides 1 H NMR spectrum;

[0025] Figure 2b The embodiment of the present invention provides 13 C carbon spectrum NMR;

[0026] Figure 3a DSC-PBAT (NC801) provided by an embodiment of the present invention;

[0027] Figure 3b DSC-PBAT (Selfprepared) provided in an embodiment of the present invention;

[0028] Figure 4 Transmission electron microscope image of the novel environmentally friendly catalyst provided by the embodiment of the present invention;

[0029] Figure 5 A scanning electron microscope image of a novel environmentally friendly catalyst provided by an embodiment of the present invention; DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0031] like Figure 1 As shown, a new environmentally friendly catalyst system, the new environmentally friendly catalyst system for PBAT synthesis includes: metal organic framework materials, organic tin compounds and surfactants.

[0032] In this embodiment, metal organic framework (MOFs) materials: MOFs materials with excellent catalytic properties are selected, such as UiO-66, MIL-101 or ZIF-8, which perform well in catalytic reactions due to their large specific surface area and adjustable chemical properties; organic tin compounds: such as dibutyltin oxide or dibutyltin dilaurate, are used to enhance the activity of the catalyst; surfactants: such as polyethylene glycol (PEG) or sodium dodecyl sulfate (SDS), are used to improve the dispersibility and stability of the catalyst.

[0033] The MOFs material is UiO-66, which has high thermal stability and catalytic activity, so that the catalyst can still maintain good performance at higher temperatures.

[0034] The organic tin compound is dibutyltin dilaurate, which exhibits a higher performance in the catalytic process. The surfactant is polyethylene glycol (PEG), which can effectively improve the dispersibility and stability of the catalyst, thereby enhancing the catalytic effect of the catalyst.

[0035] A method for preparing the novel environmentally friendly catalyst system as described above, the method comprising:

[0036] To prepare the metal organic framework material, the metal salt and the organic ligand are mixed in a solvent to obtain a uniformly dispersed suspension;

[0037] Synthesizing a metal organic framework material by a hydrothermal method, obtaining a MOFs material precursor by cooling, filtering and washing a reaction product, and drying the product at 100° C. to 120° C. in a breaking gas atmosphere to obtain a metal organic framework material;

[0038] preparing a composite catalyst, mixing the prepared metal organic framework material with an organic tin compound and a surfactant in proportion;

[0039] Ultrasonic dispersion treatment or grinding treatment is used to ensure uniform mixing of the components to form a stable catalyst system, and the catalyst is dried at 50° C. to 70° C. to obtain a final catalyst product.

[0040] In this embodiment, (1) MOFs material (i.e., metal organic framework material) is prepared by mixing a metal salt (such as a zirconium salt or a chromium salt) and an organic ligand (such as terephthalic acid or p-carboxybenzoic acid) in a suitable solvent to obtain a uniformly dispersed suspension;

[0041] (2) synthesizing MOFs material by a hydrothermal method (e.g., reacting at 160-200°C for 12-24 hours), and obtaining a MOFs material precursor by cooling, filtering and washing the reaction product, and drying it at 100°C to 120°C in an atmosphere of an annular gas;

[0042] (3) Preparing a composite catalyst, mixing the prepared MOFs material with an organic tin compound and a surfactant in proportion.

[0043] (4) Ultrasonic dispersion treatment (e.g., treatment at 20-40 kHz for 20-60 minutes) or grinding treatment is used to ensure that the components are evenly mixed to form a stable catalyst system. After the mixing and dispersion treatment, the catalyst system is dried at 50° C. to 70° C. to obtain a final catalyst product.

[0044] In the catalyst preparation process, the frequency of ultrasonic dispersion treatment is 30kHz and the time is 40 minutes to obtain the best catalyst uniformity and activity.

[0045] The catalyst drying condition is drying at 60° C. for 12 hours, which can effectively remove the solvent residue while maintaining the activity and stability of the catalyst.

[0046] A PBAT synthesis method based on the novel environmentally friendly catalyst system as described above, the method comprising preparing raw materials for PBAT synthesis, adding 1,4-butanediol, adipic acid and terephthalic acid into a reactor in a predetermined proportion, and adding an appropriate amount of the novel environmentally friendly catalyst system;

[0047] Esterification reaction: the esterification reaction is carried out at 160°C to 180°C to ensure that the esterification rate reaches 80% to 95%;

[0048] The polycondensation reaction is carried out by gradually raising the temperature to 200° C. to 230° C. under reduced pressure for 60 to 120 minutes to obtain a PBAT polymer.

[0049] Raw material preparation for PBAT synthesis: 1,4-butanediol, adipic acid and terephthalic acid are added to the reactor in a predetermined proportion. An appropriate amount of a new environmentally friendly catalyst (mass fraction of 0.02% to 0.05%) is added.

[0050] The esterification reaction is carried out at 160° C. to 180° C. to ensure that the esterification rate reaches 80% to 95%.

[0051] The polycondensation reaction is carried out by gradually increasing the temperature to 200° C. to 230° C. under reduced pressure for 60 to 120 minutes to obtain a high molecular weight PBAT polymer.

[0052] (1) Preparation of catalyst precursor

[0053] a) Dissolve a metal salt (such as a zirconium salt or a chromium salt) and an organic ligand (such as terephthalic acid or p-carboxybenzoic acid) in a solvent in a certain proportion to form a uniform solution. Place the solution in a reaction vessel and synthesize a metal organic framework (MOFs) material by a hydrothermal method (160-200°C, reaction time 12-24 hours).

[0054] b) After the reaction is completed, the mixture is cooled to room temperature, filtered and washed to obtain a MOFs material precursor, and then dried at 100-120°C.

[0055] (2) Preparation of composite catalyst:

[0056] a) MOFs material is mixed with an organic tin compound (such as dibutyltin oxide) and polyethylene glycol (PEG) in a certain proportion. The mixture is subjected to ultrasonic dispersion treatment (treatment at 40kHz for 30 minutes) or grinding treatment to make the components uniformly mixed to form a stable catalyst system.

[0057] b) drying the dispersed mixture at 50-70° C. for 12 hours to obtain a solid catalyst.

[0058] (3) Synthesis of PBAT:

[0059] a) 1,4-butanediol, adipic acid and terephthalic acid are added into a reactor in proportion as raw materials.

[0060] b) Adding an appropriate amount of a new environmentally friendly catalyst (eg, the amount of catalyst is 0.03% of the total mass of the raw materials).

[0061] c) conducting an esterification reaction at 160-180° C. to achieve an esterification rate of 80% to 95%.

[0062] d) gradually raising the temperature to 200-230° C. and carrying out polycondensation reaction under reduced pressure for 60-120 minutes to obtain a high-viscosity PBAT polymer.

[0063] (4) Post-processing and product characterization:

[0064] a) After the reaction is completed, the product is cooled to room temperature and washed with a suitable solvent to remove unreacted raw materials and by-products.

[0065] b) Use conventional methods (such as extrusion, granulation, etc.) to process PBAT polymers, and characterize the structure and properties of PBAT by means of nuclear magnetic resonance, Fourier transform infrared spectroscopy, etc. to ensure that the product meets the expected quality standards.

[0066] The polycondensation reaction time is 75 minutes to achieve the best performance of PBAT, including higher intrinsic viscosity and excellent mechanical properties.

[0067] The intrinsic viscosity of the synthesized PBAT should be in the range of 1.1 dL / g to 1.3 dL / g to meet the needs of different application fields.

[0068] The esterification reaction temperature is 170° C. to obtain the best esterification rate and reaction efficiency while reducing the generation of by-products.

[0069] The catalyst can be recovered and reused by simple physical methods (such as filtering and washing) after use, thereby further reducing production costs and environmental impact.

[0070] Embodiment 1 (new catalyst):

[0071] 1. Preparation of MOFs materials:

[0072] a) Ingredients: zirconium chloride and terephthalic acid are mixed in ethanol at a molar ratio of 1:2.

[0073] b) Reaction conditions: The mixed solution was transferred to a reactor and reacted at 180° C. for 16 hours to obtain UiO-66MOFs material.

[0074] c) Post-treatment: cooling to room temperature, filtering, washing with deionized water, and drying to obtain a MOFs material precursor.

[0075] 2. Preparation of composite catalyst:

[0076] a) Ingredients: The dried UiO-66MOFs material and dibutyltin dilaurate were mixed in a mass ratio of 1:0.03.

[0077] b) Addition: 0.1% polyethylene glycol (PEG) was added as a surfactant.

[0078] c) Treatment: Use ultrasonic dispersion equipment at a frequency of 30 kHz for 40 minutes to ensure the uniformity of the catalyst.

[0079] d) Drying: Dry the mixture at 60° C. for 12 hours to obtain a composite catalyst.

[0080] 3.PBAT synthesis:

[0081] a) Ingredients: 1,4-butanediol, adipic acid and terephthalic acid are mixed in a mass ratio of 1:1:1, and 0.03% of a composite catalyst is added.

[0082] b) Esterification reaction: The reaction was carried out at 170°C for 8 hours, and the esterification rate reached 85%.

[0083] c) Polycondensation reaction: The reaction was carried out at 220° C. for 75 minutes to obtain PBAT with an intrinsic viscosity of 1.20 dL / g.

[0084] Embodiment 2 (new catalyst):

[0085] 1. Preparation of MOFs materials:

[0086] a) Ingredients: zirconium chloride and terephthalic acid are mixed in ethanol at a molar ratio of 1:2.

[0087] b) Reaction conditions: The mixed solution was transferred to a reactor and reacted at 180° C. for 16 hours to obtain UiO-66MOFs material.

[0088] c) Post-treatment: cooling to room temperature, filtering, washing with deionized water, and drying to obtain a MOFs material precursor.

[0089] 2. Preparation of composite catalyst:

[0090] a) Ingredients: The dried UiO-66MOFs material and dibutyltin dilaurate were mixed in a mass ratio of 1:0.03.

[0091] b) Addition: 0.1% polyethylene glycol (PEG) was added as a surfactant.

[0092] c) Treatment: Use ultrasonic dispersion equipment at a frequency of 30 kHz for 40 minutes to ensure the uniformity of the catalyst.

[0093] d) Drying: Dry the mixture at 60° C. for 12 hours to obtain a composite catalyst.

[0094] 3.PBAT synthesis:

[0095] a) Ingredients: 1,4-butanediol, adipic acid and terephthalic acid are mixed in a mass ratio of 1:1:2, and 0.02% of a composite catalyst is added.

[0096] b) Esterification reaction: The reaction was carried out at 170°C for 10 hours to achieve an esterification rate of 90%.

[0097] c) Polycondensation reaction: The reaction was carried out at 210° C. for 80 minutes to obtain PBAT with an intrinsic viscosity of 1.25 dL / g.

[0098] Embodiment 3 (new catalyst):

[0099] 1. Preparation of MOFs materials:

[0100] a) Ingredients: zirconium chloride and terephthalic acid are mixed in ethanol at a molar ratio of 1:2.

[0101] b) Reaction conditions: The mixed solution was transferred to a reactor and reacted at 180° C. for 16 hours to obtain UiO-66MOFs material.

[0102] c) Post-treatment: cooling to room temperature, filtering, washing with deionized water, and drying to obtain a MOFs material precursor.

[0103] 2. Preparation of composite catalyst:

[0104] a) Ingredients: The dried UiO-66MOFs material and dibutyltin dilaurate were mixed in a mass ratio of 1:0.03.

[0105] b) Addition: 0.1% polyethylene glycol (PEG) was added as a surfactant.

[0106] c) Treatment: Use ultrasonic dispersion equipment at a frequency of 30 kHz for 40 minutes to ensure the uniformity of the catalyst.

[0107] d) Drying: Dry the mixture at 60° C. for 12 hours to obtain a composite catalyst.

[0108] 3.PBAT synthesis:

[0109] a) Ingredients: 1,4-butanediol, adipic acid and terephthalic acid are mixed in a mass ratio of 1:2:1, and 0.05% of a composite catalyst is added.

[0110] b) Esterification reaction: The reaction was carried out at 170°C for 12 hours, and the esterification rate reached 95%.

[0111] c) Polycondensation reaction: The reaction was carried out at 230° C. for 70 minutes to obtain PBAT with an intrinsic viscosity of 1.30 dL / g.

[0112] Comparative Example 1 (traditional catalyst):

[0113] 1. Catalyst preparation:

[0114] The catalyst was tetrabutyl titanate and the preparation was carried out according to the standard formula.

[0115] 2.PBAT synthesis:

[0116] a) Ingredients: 1,4-butanediol, adipic acid and terephthalic acid are mixed in a mass ratio of 1:1:1, and a conventional tetrabutyl titanate catalyst is used.

[0117] b) Esterification reaction: The reaction was carried out at 180°C for 10 hours to achieve an esterification rate of 80%.

[0118] c) Polycondensation reaction: The reaction was carried out at 270° C. for 90 minutes to obtain PBAT with an intrinsic viscosity of 1.15 dL / g.

[0119] Comparative Example 2 (traditional catalyst):

[0120] 1. Catalyst preparation:

[0121] Use traditional antimony catalysts and prepare according to standard formula.

[0122] 2.PBAT synthesis:

[0123] a) Ingredients: 1,4-butanediol, adipic acid and terephthalic acid are mixed in a mass ratio of 1:1:1, and a traditional antimony-based catalyst is used.

[0124] b) Esterification reaction: The reaction was carried out at 180°C for 8 hours, and the esterification rate reached 85%.

[0125] c) Polycondensation reaction: The reaction was carried out at 270° C. for 80 minutes to obtain PBAT with an intrinsic viscosity of 1.18 dL / g.

[0126] The tensile testing machine was used to test the mechanical properties of the samples according to GB / T 1040.1-2006. The test speed was 10mm / min. The comparison of tensile properties is shown in the following table:

[0127]

[0128]

[0129] like Figure 1 , Figure 2a , Figure 2b , Figure 3a , Figure 3b , Figure 4 and Figure 5 From the above analysis and test results, it can be seen that the PBAT prepared using the new catalyst in Examples 1, 2, and 3 is significantly better than that in Comparative Examples 1 and 2 in terms of tensile strength and elongation at break, showing the effect of the new catalyst on the improvement of the mechanical properties of PBAT. Example 3 performs best, with the highest tensile strength and elongation at break, which is in line with experimental expectations, indicating that the optimized catalyst has the best performance.

[0130] In the examples, the performance of the catalyst was optimized by adjusting the catalyst ratio, addition amount and treatment conditions, significantly improving the intrinsic viscosity of PBAT, and achieving a higher esterification rate and polycondensation efficiency at a lower reaction temperature. Comparative cases show that traditional catalysts require higher reaction temperatures and longer times to obtain lower esterification rates and intrinsic viscosities. The optimization results show that the new catalyst has obvious advantages in efficiency and economy.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A new environmentally friendly catalyst system, characterized in that: The novel environmentally friendly catalyst system for synthesizing PBAT comprises: a metal organic framework material, an organic tin compound and a surfactant.

2. The novel environmentally friendly catalyst system according to claim 1, characterized in that: The metal organic framework material is UiO-66, MIL-101 or ZIF-8, the organic tin compound is dibutyltin oxide or dibutyltin dilaurate, and the surfactant is polyethylene glycol or sodium dodecyl sulfate.

3. A method for preparing the novel environmentally friendly catalyst system according to claim 1 or 2, characterized in that: The method comprises: To prepare the metal organic framework material, the metal salt and the organic ligand are mixed in a solvent to obtain a uniformly dispersed suspension; Synthesizing a metal organic framework material by a hydrothermal method, obtaining a MOFs material precursor by cooling, filtering and washing a reaction product, and drying the product at 100° C. to 120° C. in a breaking gas atmosphere to obtain a metal organic framework material; preparing a composite catalyst, mixing the prepared metal organic framework material with an organic tin compound and a surfactant in proportion; Ultrasonic dispersion treatment or grinding treatment is used to ensure uniform mixing of the components to form a stable catalyst system, and the catalyst is dried at 50° C. to 70° C. to obtain a final catalyst product.

4. The method for preparing the novel environmentally friendly catalyst system according to claim 3, characterized in that: In the step of using ultrasonic dispersion treatment, the frequency of ultrasonic dispersion treatment is 30 kHz and the time is 40 minutes.

5. The method for preparing the new environmentally friendly catalyst system according to claim 3, characterized in that: In the step of drying at 50°C to 70°C to obtain the final catalyst product, the drying condition is drying at 60°C for 12 hours.

6. A PBAT synthesis method based on the new environmentally friendly catalyst system as claimed in claim 1 or 2, characterized in that: The method comprises preparing raw materials for PBAT synthesis, adding 1,4-butanediol, adipic acid and terephthalic acid into a reactor in a predetermined ratio, and adding an appropriate amount of a new environmentally friendly catalyst system; Esterification reaction: the esterification reaction is carried out at 160°C to 180°C to ensure that the esterification rate reaches 80% to 95%; The polycondensation reaction is carried out by gradually raising the temperature to 200° C. to 230° C. under reduced pressure for 60 to 120 minutes to obtain a PBAT polymer.

7. The PBAT synthesis method according to claim 6, characterized in that: The polycondensation reaction time was 75 minutes, and the esterification reaction temperature was 170°C.